Barrierefreie Stationen im Schienenverkehr. Rechtlicher Rahmen und Handlungsbedarf in Deutschland. - Becker, Josef; Hollborn, Hans-Joachim; Schramm, Elke (Deutscher Verkehrs-Verlag, 2004)
Das "Gesetz zur Gleichstellung behinderter Menschen und zur Änderung anderer Gesetze" [2002] hat die rechtliche Grundlage für den Anspruch auf barrierefreie Gestaltung aller Lebensbereiche geschaffen. Von einer Barrierefreiheit, die neben den behinderten auch vielen anderen mobilitätseingeschränkten Menschen zugute kommt, ist der Schienenpersonennahverkehr aber noch weit entfernt. Dabei haben die verschiedenen Gruppen mobilitätseingeschränkter Menschen durchaus unterschiedliche Anforderungen an die Gestaltung von Bahnanlagen. difu

The law that ensures 'the equality of handicapped people and changes to other laws' incorporates the right of unhindered access for, and equal status of, handicapped people. The intention is to allow such people to move about without undue restrictions also in the case of railway stations. This law tends to have in impact on other laws and regulations. Full implementation still leaves much work to be done, especially in more than half of all railway stations across Germany. Attention has to be paid to the needs of the various handicapped persons' user groups, which means that special plans have to be developed and implemented. The high level of expense associated with providing better facilities, and the time factor linked to their implementation, shows that related problems will be confronted for some time. A commonly supported initiative is wanted to combine the efforts of all the service providers and install the easy access facilities needed. difu
Keywords: Öffentlicher Verkehr; Schienenverkehr; Bahnhof; Behinderter; Mobilität; Gemeinde; Bundesland; Bahngesellschaft; Landesgleichstellungsgesetz; Behindertengleichstellung; Handlungsbedarf; Barrierefreiheit; Barrierefreies Bauen; Gemeindefinanzierungsgesetz